Skeletal muscle salt inducible kinase 1 promotes insulin resistance in obesity - Mark Nixon; Randi Stewart-Fitzgibbon; Jingqi Fu; Dmitry Akhmedov; Kavitha Rajendran; Maria G. Mendoza-Rodriguez; Yisel A. Rivera-Molina; Micah Gibson; Eric D. Berglund; Nicholas J. Justice; Rebecca Berdeaux (Molecular Metabolism, 2016)
Objective: Insulin resistance causes type 2 diabetes mellitus and hyperglycemia due to excessive hepatic glucose production and inadequate peripheral glucose uptake. Our objectives were to test the hypothesis that the proposed CREB/CRTC2 inhibitor salt inducible kinase 1 (SIK1) contributes to whole body glucose homeostasis in vivo by regulating hepatic transcription of gluconeogenic genes and also to identify novel SIK1 actions on glucose metabolism. Methods: We created conditional (floxed) SIK1-knockout mice and studied glucose metabolism in animals with global, liver, adipose or skeletal muscle Sik1 deletion. We examined cAMP-dependent regulation of SIK1 and the consequences of SIK1 depletion on primary mouse hepatocytes. We probed metabolic phenotypes in tissue-specific SIK1 knockout mice fed high fat diet through hyperinsulinemic-euglycemic clamps and biochemical analysis of insulin signaling. Results: SIK1 knockout mice are viable and largely normoglycemic on chow diet. On high fat diet, global SIK1 knockout animals are strikingly protected from glucose intolerance, with both increased plasma insulin and enhanced peripheral insulin sensitivity. Surprisingly, liver SIK1 is not required for regulation of CRTC2 and gluconeogenesis, despite contributions of SIK1 to hepatocyte CRTC2 and gluconeogenesis regulation ex vivo. Sik1 mRNA accumulates in skeletal muscle of obese high fat diet-fed mice, and knockout of SIK1 in skeletal muscle, but not liver or adipose tissue, improves insulin sensitivity and muscle glucose uptake on high fat diet. Conclusions: SIK1 is dispensable for glycemic control on chow diet. SIK1 promotes insulin resistance on high fat diet by a cell-autonomous mechanism in skeletal muscle. Our study establishes SIK1 as a promising therapeutic target to improve skeletal muscle insulin sensitivity in obese individuals without deleterious effects on hepatic glucose production.